A non-uniform cellular automata framework for topology and sizing optimization of truss structures subjected to stress and displacement constraints. (1st January 2021) - El Bouzouiki, Mohamed; Sedaghati, Ramin; Stiharu, Ion
Highlights: A new non-uniform Cellular Automata (CA) algorithm is proposed. The proposed algorithm explores a larger design space than uniform CA algorithms. An improved version of the FSD/FUD strategy at the cell level has been implemented. The efficiency and accuracy of the proposed new CA algorithm are demonstrated. Abstract: The conventional Cellular Automata (CA) approach has the disadvantage of being particularly suited for design optimization of uniform truss ground structures with identical cells. Moreover, the conventional CA algorithms, which are intrinsically local, have to be modified in order to be able to tackle problems involving displacement constraints. This paper presents a new non-uniform Cellular Automata algorithm, which is based on non-identical cells and a modified FSD/FUD approach. The new algorithm can solve the minimum weight optimization problem of truss structures including both stress and displacement constraints. The efficiency and accuracy of the proposed methodology are proved on a number of benchmark truss design problems.